2010
DOI: 10.1186/1475-2859-9-73
|View full text |Cite
|
Sign up to set email alerts
|

Single cell oils of the cold-adapted oleaginous yeast Rhodotorula glacialis DBVPG 4785

Abstract: Background The production of microbial lipids has attracted considerable interest during the past decade since they can be successfully used to produce biodiesel by catalyzed transesterification with short chain alcohols. Certain yeast species, including several psychrophilic isolates, are oleaginous and accumulate lipids from 20 to 70% of biomass under appropriate cultivation conditions. Among them, Rhodotorula glacialis is a psychrophilic basidiomycetous species capabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
85
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 24 publications
13
85
0
1
Order By: Relevance
“…Another reason of this decrease can be attributed to the conversion of stored lipids into citric acid, as reported by Makri et al 54 Th ese results are in good agreement with those reported by investigators, who show that incubation time strongly aff ects the cell growth and lipid accumulation in diff erent oleaginous microorganisms including the yeast Y. lipolytica. 5,49,54,55…”
Section: Effect Of Additional Carbon and Nitrogen Sources On Biomass mentioning
confidence: 99%
See 3 more Smart Citations
“…Another reason of this decrease can be attributed to the conversion of stored lipids into citric acid, as reported by Makri et al 54 Th ese results are in good agreement with those reported by investigators, who show that incubation time strongly aff ects the cell growth and lipid accumulation in diff erent oleaginous microorganisms including the yeast Y. lipolytica. 5,49,54,55…”
Section: Effect Of Additional Carbon and Nitrogen Sources On Biomass mentioning
confidence: 99%
“…However, there is only one report on the production of lipids by cold-adapted oleaginous yeasts, with the aim to develop a novel potential alternative feedstock for biodiesel industry. 5 Cheese whey is a green-yellowish liquid resulting from the precipitation and removal of milk casein in cheese making processes. Although several possibilities of cheese whey utilization have been explored, a major portion of the world cheese whey production is discarded as effl uent.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The FAs C18:2(n-6), linoleic acid and C18:3(n-3), alpha-linolenic acid are essential to all higher animals. Usually, the degree of unsaturation increases Applied Biochemistry in yeasts with decreasing cultivation temperature [e.g., [7][8][9]. However, in some cases, it has also been observed that the saturation degree remained constant or even decreased at lower temperature, instead of an increase of the C16:C18 ratio that has been observed at lower temperatures [10,11].…”
Section: Introductionmentioning
confidence: 99%